Capital in Spain, 1850–2019 - Prados de la Escosura, Leandro (Cliometrica, 2022)
Abstract: The rising trend in the capital-output ratio and the productivity slowdown have put capital back in the economist’s agenda. This paper contributes to the debate by providing new estimates of net capital stock and services for Spain over the last 170 years. The net capital (wealth) stock-GDP ratio rose over time and doubled in the last half a century. Capital services grew fast over the long run accelerating in the 1920s and from the mid-1950s to 2007. Until 1975, its acceleration was helped by an increase in the “quality” of capital. Capital deepening proceeded steadily, accelerating during 1955–1985 and slowing down thereafter for expanding sectors attracted less investment-specific technological progress. Although capital consumption rose over time, the rate of depreciation fell from 1970 to 2007 as new capital goods’ relative prices declined due to embodied technological change.